Penilaian Postur Kerja Menggunakan Metode Quick Exposure Checklist (QEC) di IKM Tahu Sari Murni - Dian Pambayung; Bambang Suhardi; Rahmaniyah Dwi Astuti (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
Working in a standing position consumes energy by 10% -15% compared to work done in a sitting position. If the posture stays for a prolonged period, then the health of the worker may be disrupted and affect production activity.IKM (Small and Medium Industry) Tahu Sari Murni is one of the tofu processing industries located in Krajan RT.03 / RW.03 Mojosongo, Surakarta. All workers, working on a standing position with awkward posture such as lifting, bending, and standing for 7-8 hours. Therefore, an awkward posture risk assessment using the QEC method needs to be done to determine the occupational risks faced by the worker.The results show that only the soybeans washing station that categorized at the